Implementasi Nilai-Nilai Tasawuf Dalam Membentuk Karakter Santri Di Era Globalisasi Di Pondok Pesantren Majma’al Bahroin Hubbul Wathon Minal Iman Losari Ploso Jombang - Aziz, Fuad; jumari; Salim, M. Nur (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam, Universitas Hasyim Asy'ari Tebuireng Jombang, Indonesia, 2024)
Sufismiis aiscientific discipline thatistudies theigood andibad ofitheisoul, as well as how to cleanse it of bad things and fill it with good qualities. This is done by performing suluk and journeying towards (the pleasure of) Allah SWT and leaving (prohibitions) towards (his commands). The Majma'al Bahrain Islamic Boarding School teaches the values of Sufism, leading students to have good and commendable behavior. Theiaim ofithe researchiis toifind outiwhether theimorals of Sufism which really need to be implemented in this era of globalization, whether the students have implemented them, to find out whether in the boarding school there has been a study of the values of Sufism apart from learning to recite the Koran and classical books and to find out how determined santri in tolabul ilmi at the cottage. This research method is taken from qualitativeiresearch methods,iresearch that isidescriptive ininature and tendsito useianalysis. Theitheoretical basisiis also usedias aiguide soithat theifocus ofithis qualitativeresearchi method is correct in accordance withithe factsiin theifield. not talking about facts but the facts are talking. Theiresults ofithe research areithat students in Islamic boarding schools, apart from studying the Koran and classical books, also need to instill the values of Sufism because apart from faith and Islam in religious teachings there is also ihsan, cultivating everyday traits such as zuhud, wara and sincerity will make students get blessings. knowledge for the future. The application of the values of repentance, asceticism, patience and wira'i will continue to be taught and practiced in the teachings of the Majma'aliBahroin HubbuliWathonMinaliIman LosariiPloso Jombang Islamic Boarding School, in this era of globalization character formation is not based on cleanliness values Therefore, it is feared that there will be a wrong intention in seeking knowledge, so researchers are taking part in ensuring that this does not happen among studentsiin theiera of globalization iniIslamic boarding schools.i